Предмет: Алгебра,
автор: morgan3361
1. Упростите выражения: а) 2х - 5 + (4 - 3х); 6) 2x - 5 - (4 - 3x); в) 2x + 5(4 - 3х); г) 2x - 5(4 - 3х); д) 2х5 - (4 - 3х).
Ответы
Автор ответа:
2
Объяснение:
2х-5+(4-3х)=2х-5+4-3х=-1х-1
2x-5-(4-3x)=2х-5-4+3х=5х-9
2x+5(4-3х)=2х+20-15х=20-13х
2х*5-(4-3х)=10х-4+3х=13х-4
Похожие вопросы
Предмет: Русский язык,
автор: RomanLexik1
Предмет: Русский язык,
автор: POMOGITE771
Предмет: Русский язык,
автор: рамазан2225
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: nbyshik